Consumer preferences on the Ukrainian market of liqueurs. The review - Bozhko, Tatyana (Engineering Sciences And Technologies, 2014)
The aim of the paper is to analyze the market of alcoholic beverages in Ukraine and to identify the directions of expanding the range of these products by developing new recipes of enriched mix drinks (with fitoletsytyne, chicory and skimmed milk). The article presents the classification of liqueur drinks in Ukraine. It highlights the role of the quality of raw materials used for the production of liqueurs in Ukraine nowadays. Great attention was also paid to the study of consumer preferences on liqueurs segment
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2014, Nr 2 (13), s. 14-24
Keywords: liqueur; commodity classification of liqueur-vodka products; consumer preferences; likiery; towaroznawcza klasyfikacja produktów „likiery-wódki”; preferencje konsumentów